ASSESSMENT OF THE CLINICAL EFFECTIVENESS OF MINERAL TRIOXIDE AGGREGATE (MTA) IN THE TREATMENT OF PULPITIS IN CHILDREN WITH PRIMARY DENTITION FOLLOWING ORTHODONTIC TREATMENT (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Pediatric dentistry and orthodontics are closely related fields. Children’s teeth perform not only the chewing function, but also the function of maintaining space for permanent teeth. International studies have shown that early extraction of children’s molars can cause mesial displacement of adjacent teeth within 6 months (Northway et al., 1984). This increases the risk of space deficiency and malocclusion during the eruption of permanent teeth.